Developing Primary School Students’ Environmental Literacy by Utilizing Scraps - Kuswendi, Uus; Arga, Hana Sakura Putu (Mimbar Sekolah Dasar, 2020)
One aspect of environmental literacy is that there is an action from someone who is trying to reduce environmental pollution. For primary school students, this effort can be done by processing dry waste into useful items. Processed garbage can be made into scraps that sell for sale or just simple handicrafts. This research was aimed at developing environmental literacy through the use of scraps in primary schools. The research employed a quantitative approach with quasy experimental method. The sample of the research was fifth grade primary school students who were randomly selected. Then the data collection techniques were conducted with the cognitive tests, practice, and attitude questionnaires. Meanwhile, data analysis process employed the inference statistics. The results showed that the activity of utilizing scrap affected the environmental literacy of the students. The aspect that experienced a quite good change was the performance aspect in the form of carrying out used scrap activities. Therefore, the use of scraps could be an effort to build the environmental literacy of primary school students.